2015
DOI: 10.1097/acm.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

Discordance Between Resident and Faculty Perceptions of Resident Autonomy

Abstract: Faculty and residents had discordant perceptions of resident autonomy and of faculty support for resident autonomy. When faculty restrict the independence of "passive" residents whose competence they question, residents may receive fewer opportunities for active learning. Strategies that support autonomy, such as scaffolding, may help residents gain confidence and competence, enhance residents' relatedness to team members and supervisors, and help programs adapt to accreditation requirements to foster resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 34 publications
0
26
0
1
Order By: Relevance
“…Several studies and opinion papers have highlighted the loss of autonomy in current clinical educational settings and have discussed its educational impact [ 13 17 ]. Some suggest that increased faculty oversight has led to a decline in resident understanding of ownership [ 6 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies and opinion papers have highlighted the loss of autonomy in current clinical educational settings and have discussed its educational impact [ 13 17 ]. Some suggest that increased faculty oversight has led to a decline in resident understanding of ownership [ 6 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that there is only a minimal curriculum implemented in SDT constructs is, to some degree, remarkable since: a) in the practice of health care practitioners, several examples can be found of interventions that actually utilize (elements of) SDT in several (psycho)pathologically and/or lifestyle related issues [ 7 ]. Obviously, practitioners are more proactive than curriculum developers; b) several curricula do use SDT constructs for motivating their own students [ 20 ] as commented by Hoffman (2015) [ 21 ] for promoting techniques like scaffolding. From this, it can be concluded that, in the field of education and training of medical practitioners, there is sufficient familiarity with SDT constructs per se; what is needed, however, is a renewed perspective of the classical communication model using Huber’s “to adapt and to self-manage” [ 5 ] as a starting point for defining learning outcomes in curricula on the training and education of these practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of description of the best principles for doing this [13], few initiatives consider and measure the effect of interventions catered to enhance student motivation in medical education [14], especially so in undergraduate medical curricula. The theoretical framework for this study is based on the Self-determination Theory (SDT).…”
Section: Introductionmentioning
confidence: 99%